Analysis Management Risk Technology Information on CV. Aren Jaya Use ISO 31000:2018 - Muhamad Rizky; Faaza Bil Amri (International Journal of Electrical Engineering, Mathematics and Computer Science, 2024)
CV. Aren Jaya is an AC service provider located in South Tangerang. In 2017 this shop began to develop by opening new and used AC sales services, AC installation services, used washing machine sales services and washing machine service services. In carrying out the company's business process activities, of course there will always be possible risks and potential risks that can threaten and disrupt business process activities. The need for a risk analysis of existing IS/IT resources in the company, using the ISO 31000:2018 method related to risk management. The purpose of this study is to minimize all possible risks that are currently being experienced or will also occur and provide appropriate recommendations regarding risks that may occur at any time. The research method used in the risk analysis uses the ISO 31000:2018 framework. The results of this risk analysis are in the form of an analysis of the possibility of existing risks, evaluations and risk mitigation plans so that they can produce improvements to existing risks. The final result of the research produces risk recommendations, so the company can adjust to the priorities of the existing risk level, so that it does not interfere with business activities at CV. Arena Jaya.